Coordination polymers of 5-substituted isophthalic acid. Issue 7 (21st December 2015) - McCormick, Laura J.; Morris, Samuel A.; Slawin, Alexandra M. Z.; Teat, Simon J.; Morris, Russell E.
Abstract : Crystallographic investigations were conducted into coordination polymers derived from 5-methyl, 5-methoxy and 5- tert -butyl isophthalic acids. Preliminary nitric oxide storage and release properties are also reported. Abstract : The synthesis and characterisation of five coordination polymers – Ni2 (mip)2 (H2 O)8 ·2H2 O (1 ), Zn6 (mip)5 (OH)2 (H2 O)4 ·7.4H2 O (2 ), Zn6 (mip)5 (OH)2 (H2 O)2 ·4H2 O (3 ), Mn(HMeOip)2 (4 ), and Mn3 (tbip)2 (Htbip)2 (EtOH)2 (5 ) – are reported. Preliminary nitric oxide release data on compounds2 and3 are also given.